Meningkatkan Hasil Belajar Siswa Pada Konsep Bangun Ruang Melalui Cooperatif Learning Berbasis Open-Ended Berbantuan Alat Peraga Kelas V SD - Edumatica FKIP; betrri yustinaningrum (Universitas Jambi, 2017)
Based on preliminary observations through interviews with teachers of grade V SDN 2 Candisari said that learning of geometry in particular concerning netting geometry and congruency still low. To overcome this problem has been studied action whose purpose enhance the activity and the number of students who completed their academic achievement with the use of cooperative learning models based on Open-ended aided by props subject of geometry grade V SDN 2 Candisari. The variable in this study is the activity of the student and student achievement. This research was conducted by two of cycles. From the research activity of students 67.10% in first cycle and 72.40% in second cycle, the average student achievement in first cycle was obtained 76.15 and 83.05 in the second cycle, while learning completeness students obtained 76.92% (not finished) in first cycle and 88.46% (complete) in second cycle. It can be concluded that the use of cooperative learning models based on Open-ended aided by props subject of geometry can enhance the activity and student achievement.